Pendugaan Umur Simpan Kerupuk Opak Singkong Dengan Metode Accelerated Shelf Life Testing (ASLT) Model Arrhenius - Ramadhan, Muhammad Alghifari; Elfiana, Elfiana; Irwan, Irwan (Politeknik Negeri Lhokseumawe, 2025)
Shortening is a fat product used in the food industry to improve the texture and quality of the final product. The use of vegetable fats and olein as raw materials offers a healthier and environmentally friendly alternative to animal fats. This research aims to develop a shortening emulsifier formula made from stearin and olein using lecithin, to increase product stability and quality. In this research, white butter (shortening) was made using raw materials that had gone through neutralization, bleaching, deodorization and fractionation methods, and the final result of the white butter product used a mixing method, namely by mixing olein and stearin produced from the Teaching Factory laboratory, with raw materials 50 g olein and 100 g stearin, by varying the lecithin content, namely 2.5 g, 3.0 g, 3.5 g, 4.0 g, 4.5 g and with stirring time for 3.5 minutes, 4 .0 minutes, 4.5 minutes, 5.0 minutes, 5.5 minutes. The best results were obtained at a lecithin level of 3.0 grams and a stirring time of 5.0 minutes. With a melting point value of 49.5°C, water content of 0.19%, free fatty acids of 0.19%, these values meet SNI. and organoleptic with an average value of 4.3 (very bright) for color, 4.6 (very not rancid) for aroma, and 3.7 (very soft) for texture. From the results of the microbial contamination test, there were 7 colonies in the sample with a lecithin content of 3.0 g with a stirring time of 5.0 minutes, and 6 colonies in the 4.0 g sample with a stirring time of 5.5 minutes. This value still meets the SNI standard for shortening against microbial contamination, namely 10 Apm/gram.